Dam spillways and the SPH method: two case studies in Portugal. Issue 3 (3rd July 2019) - Moreira, Andreia; Leroy, Agnès; Violeau, Damien; Taveira-Pinto, Francisco
Abstract : In this paper, the SPH (Smoothed Particle Hydrodynamics) method is applied to predict the flow features in dam spillways and energy dissipators. Two study cases were simulated using the 3D WCSPH code, GPUSPH: the hydraulic jump in the Crestuma dam and the flow in the new spillway of the Caniçada dam, both located in the North of Portugal. An extensive quantitative validation was carried out - water depths were computed with a reasonable accuracy, yet, its accuracy seemed to be dependent upon the existing flow features, and the evolution of pressures in the spillway channel was generally well captured, thanks to the Unified Semi-Analytical Wall boundary conditions technique. Comparison between SPH and a finite-volume approach results is also presented. Lastly, a set of practical recommendations for the application of SPH to model dam spillways is given, based on the experience attained.